2013
DOI: 10.1182/blood-2013-06-510453
|View full text |Cite
|
Sign up to set email alerts
|

Detailed characterization of multiple myeloma circulating tumor cells shows unique phenotypic, cytogenetic, functional, and circadian distribution profile

Abstract: Key Points• Detailed characterization of myeloma circulating tumor cells shows that these represent a unique subpopulation of BM clonal PCs.• Myeloma CTCs are clonogenic, quiescent, and may represent an ancestral clone potentially driven by circadian rhythms.Circulating myeloma tumor cells (CTCs) as defined by the presence of peripheral blood (PB) clonal plasma cells (PCs) are a powerful prognostic marker in multiple myeloma (MM). However, the biological features of CTCs and their pathophysiological role in MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
162
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(175 citation statements)
references
References 50 publications
(64 reference statements)
11
162
0
2
Order By: Relevance
“…37 In line with this hypothesis, we recently showed that MM circulating tumor cells represent a singular phenotypic and functional subset of MM tumor cells characterized by lower CD138 expression 22,38 Here, we used new analytic tools developed by the EuroFlow Consortium 20 to simultaneously evaluate the pattern of expression of 23 markers at the single-cell level and longitudinally compare the iPEPs from diagnostic vs MRD clonal PCs. In contrast to the abovementioned hypothesis, our results demonstrate that MM cells with stronger capacity to survive frontline chemotherapy were those with the highest expression of CD138; because MRD clonal PCs are responsible for the disease relapse, these results point out the clonogenic potential of mature CD138…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…37 In line with this hypothesis, we recently showed that MM circulating tumor cells represent a singular phenotypic and functional subset of MM tumor cells characterized by lower CD138 expression 22,38 Here, we used new analytic tools developed by the EuroFlow Consortium 20 to simultaneously evaluate the pattern of expression of 23 markers at the single-cell level and longitudinally compare the iPEPs from diagnostic vs MRD clonal PCs. In contrast to the abovementioned hypothesis, our results demonstrate that MM cells with stronger capacity to survive frontline chemotherapy were those with the highest expression of CD138; because MRD clonal PCs are responsible for the disease relapse, these results point out the clonogenic potential of mature CD138…”
Section: Discussionmentioning
confidence: 94%
“…Then, the iPEP of diagnostic (baseline) and chemoresistant (MRD) cells for all 23 phenotypic markers analyzed plus FSC and SSC was generated for every single clonal PC, after merging of flow cytometry data files and calculation of data. 21,22 First, the merge function of the Infinicyt software (Cytognos SL, Salamanca, Spain) was used to fuse the different data files corresponding to the 4 different 8-color mAb combinations studied per sample into a single data file containing all information measured for that sample. For any single cell in each 8-color mAb combination (aliquot), this included data about those antigens that were measured directly on it and antigens that were not evaluated directly (missing values) for that cell in the corresponding aliquot it was contained in.…”
Section: Generation Of Immunophenotypic Protein Expression Profilesmentioning
confidence: 99%
“…Therefore, we performed phenotypic characterization of tested myeloma cell lines after exposure to the inflammatory conditions with focus on the RPMI 8226 cells. Overall, we analysed expression of selected 13 cell surface markers which used to be employed for characterization of MM-cell phenotype, e.g., CD19, CD20, CD28, CD38, CD45, CD49e, CD49d, CD54, CD56, CD117, CD138, CD184, HLA-DR [4]. Noticeable differences were detected in expression of three CD markers, specifically CD38, CD138, CD45, and to certain extent CD20, as well.…”
Section: Resultsmentioning
confidence: 99%
“…Actually, some studies have demonstrated the presence of circulating PCs in more than 70% of patients with MM [3]. Very recent study by Paiva et al [4] elegantly showed that circulating myeloma tumor cells, as defined by the presence of peripheral blood clonal PCs, might be even a powerful prognostic marker in MM. However, in some patients with MM, the PCs proliferation escapes the BM microenvironment influences and it results in extramedullary disease (EMD), which can constitute the most prominent clinical feature of the disease [5].…”
mentioning
confidence: 99%
“…Circulating neoplastic PCs are thought to be independent of the bone marrow microenvironment and have a lower expression of adhesion molecules and integrins. 25 Although circulating PCs did not correlate with an increase in medullary abnormalities in the AS (P 5 .220) ( Table 1) …”
Section: Org Frommentioning
confidence: 99%